30.9k views
2 votes
PLEASE HURRY. I NEED THIS IS LIKE 20 MINUTES AT THE MOST. I GET AN F IF I DON'T HAVE AN ANSWER.

Which expression is equivalent to the expression shown below?


20 + 8y - 9y - 21


Select each correct answer.


2(10 + 4y - 7y - 19)


2(10 + 4y) - 3(3y - 7)


4(5 + 2y - 5y - 17)


4(5 + 2y) - 3(3y + 7)


-(y + 1)


-(1 - y)


y - 1

User Mefitico
by
4.7k points

1 Answer

2 votes

Answer:

4(5+2y)=3(3y+7) and -(y+1)

Explanation:

You combine like terms

20-21 =-1

8y -9y = -1y

so your answer is anything that is the same as -1 - y

2(10+4y-7y-19) =2( -3y-9) = -6y-18 NO

2(10 +4y) - 3(3y-7) = 20 +8y - 9y +21 = -y +41 NO

4(5+2y-5y-17)= 4(-3y -12) = -12y -48 NO

4(5+2y) - 3(3y+7) = 20 +8y - 9y -21 = -1 = y YES

-(y+1)= -y-1 YES

-(1-y) = -1+y NO

User BoazGarty
by
5.2k points